Megaesophagus. Thal operation - Silva, Celso; Estapé, Gonzalo (Cirugía del Uruguay, 1975)
The. authors report a case of advanced achalasia of the esophagus, treated by an abdominal approach, by means of a fundic patch operation (Thal's technique). Clínica! improvement was only partía!; the dysphagia for solids persisted. Considerations are made on the procedures of Thal, Grondhal, Heyrosky, Wangensteen and Maillet, concluding that, so far, there is no efficient technique to solve the advanced cases of this disease.